Molten salt power towers operating at 600–650 °C: Salt selection and cost benefits. (April 2018) - Turchi, Craig S.; Vidal, Judith; Bauer, Matthew
Highlights: sCO2 Brayton cycle can decrease the cost of concentrating solar power. Receiver efficiency and thermal storage cost may limit the advantages of the sCO2 cycle. Pure NaNO3 salt offers cost advantages if its thermal stability can be enhanced. Ternary chloride is the best of the alternative salts examined for T ≥ 650 °C. Best cases had ∼10% reduction in levelized cost of energy vs. current state of the art. Abstract: This analysis examines the potential benefit of adopting the supercritical carbon dioxide (sCO2 ) Brayton cycle at 600–650 °C compared to the current state-of-the-art power tower operating a steam-Rankine cycle with solar salt at approximately 574 °C. The analysis compares a molten-salt power tower configuration using direct storage of solar salt (60:40 wt% sodium nitrate: potassium nitrate) or single-component nitrate salts at 600 °C or alternative carbonate- or chloride-based salts at 650 °C. The increase in power cycle efficiency offered by the sCO2 Brayton cycle is expected to reduce the size and cost of the solar field required for a given thermal energy input. Power cycle capital cost is expected to decrease compared to the superheated steam-Rankine cycle, based on projections from sCO2 cycle developers. Maximizing the ΔT of the storage system is required for viable deployment of sensible-salt TES. In this regard, the partial-cooling sCO2 cycle is noted as a better option than the recompression sCO2 cycle. In the current analysis it is assumed that a ΔT = 180 K can be achieved with the partial-cooling cycle. Even with ΔT = 180 K, the potential benefits of the sCO2 Brayton cycle are partially or completely offset by increased thermal storage cost, albeit for reasons that differ for the different salts. An approximate 5% reduction in levelized cost of energy (LCOE) is achieved with either solar salt at 600 °C or ternary magnesium chloride salt at 650 °C. The potential of using pure sodium nitrate or potassium nitrate is considered because the cold tank temperature for the sCO2 power cycle is estimated at 420 °C, which would allow use of a salt with a higher melting point than solar salt. Sodium nitrate is the most cost effective, resulting in an overall LCOE reduction of 8.5%; however, sodium nitrate is known to have lower thermal stability than potassium nitrate. The strong influence of salt cost and hot-tank cost on overall economics led to the analysis of single-tank thermocline options. The thermocline design significantly reduces salt inventory (by 50% or more) and in many cases also reduces the tank size versus the hot salt tank of the 2-tank system. It is speculated that integration of encapsulated phase-change material (PCM) in the thermocline could further increase the thermal-storage energy density and reduce storage tank volume. The thermocline cases led to three scenarios with relative LCOE reductions of approximately 10%; however, this must be tempered by possible operational inefficiencies of the thermocline temperature profile.